Effect of Soaking Time and Gibberellin Concentration on Viability and Vigor of Expired Red Chili (Capsicum Annum L.) Seeds - Kamal, Muhammad; Faisal, Faisal; Hafifah, Hafifah; Rafli, Muhammad; Hendrival, Hendrival (Journal of Tropical Horticulture, 2021)
Chili is included in horticultural commodities cultivated by Indonesian farmers. Red chilies are annual shrubs classified as vegetables the community needs as kitchen necessities. Expired seeds are seeds that have experienced a decline in growth and yield. Growth hormones can be used to increase the existing hormone levels and seed germination. Gibberellins are plant growth regulators that accelerate seed germination. Gibberellin is an essential organic compound in seed germination because it controls the process. The research was conducted to determine the effect of Gibberellins concentration and soaking time on the viability and vigor of expired red chili seeds. This research used a completely randomized design (CRD) with two factors. The first factor is the soaking time (P), which consists of 3 levels: 4 hours soaking (P1), 8 hours soaking (P2), and 12 hours soaking (P3). The second factor was the concentration of gibberellins (K), which consisted of 4 levels, which are 0 ppm (K0), 100 ppm (K1), 200 ppm (K2) and 300 ppm (K3).